Removal of Excessive Nitrogen and Phosphorus from Urban Wastewater Using Local Microalgal Bloom (Journal of Engineering Science, 2022)
The organic content from urban wastewater is treated with various conventional processes efficiently. However, for biological treatment of secondary effluent containing excessive inorganic nitrogen and phosphorus, microalgae can be used. In this study, algal strains have been collected from locally available natural blooms and cultured in a BG-11 medium. Spirulina sp., the blue-green algae, dominant over the other species within the natural bloom, is applied in ten different dosages (0.2-2.5 g/L) to the synthetic wastewater with a 3-day hydraulic retention time. The removal efficiency of nitrate, ammonia, and phosphate have been observed to be about 60%, 30%, and 54% respectively. The highest removal efficiency has been found at 2.5 g/L of microalgae dose. Linear forms of Langmuir and Freundlich isotherms have been used for biosorption modeling, and both isotherms fit well with R2>60% and NRMSE